The value of small, natural and man‐made wetlands for bird diversity in the east Colombian Piedmont. Issue 1 (2nd November 2017) - Murillo‐Pacheco, Johanna; López‐Iborra, Germán M.; Escobar, Federico; Bonilla‐Rojas, Wilian Fernando; Verdú, José R.
Abstract: Small wetlands are considered a refuge for biodiversity, but the importance of natural and man‐made lentic wetlands for the maintenance of bird diversity in human‐dominated landscapes is not well‐known in the Neotropics. This study evaluated the influence of the types and origins (natural or man‐made) of lentic wetlands on bird diversity of three guilds (aquatic, semi‐aquatic and landbirds) in the Meta Piedmont, Colombia. The species richness and the structure and composition of each bird guild were estimated and compared between and within wetland types (swamps, heronries, rice fields, semi‐natural lakes, constructed lakes and fish farms) and origins (natural, mixed and artificial). In total, 275 bird species were recorded (196 landbirds, 60 aquatic birds and 19 semi‐aquatic birds). Local species richness had a wide variation (39 to 144 species), and total and mean richness were significantly different between among wetland types and origins. Semi‐natural lakes were the most diverse wetland type, and heronries were the least diverse. Mixed‐origin wetlands had the highest species richness. The cattle egret ( Bubulcus ibis ) was the most abundant species, while heronries and rice fields showed the greatest total bird abundance. Bird diversity is strongly related to type and origin of wetlands, with significant variations in species composition among different types, which show high local and landscape heterogeneity. It is suggested that small lentic wetlands, whether natural, mixed or artificial, are important for the maintenance of local and regional bird diversity. Conservation and management actions are required to preserve wetland heterogeneity and the birds associated with it.